A revised framework of information security principles - Teixeira, André (2013)
Confidentiality, Integrity and Availability are referred to as the basic principles of Information Security. These principles have remained virtually un-changed over time, but several authors argue they are clearly insufficient to pro-tect information. Others go a step further and propose new security principles, to update and complement the traditional ones. Prompt by this context, the aim of this work is to revise the framework of Information Security principles, making it more current, complete, and comprehensive. Based on a systematic literature re-view, a set of Information Security principles is identified, defined and character-ized, which, subsequently, leads to a proposal of a Revised Framework of Infor-mation Security Principles. This framework was evaluated in terms of completeness and wholeness by intersecting it with a catalog of threats, which re-sulted from the merger of four existing catalogs. An initial set of security metrics, applied directly to the principles that constitute the framework, is also suggested, allowing, in case of adverse events, to assess the extent to which each principle was compromised and to evaluate the global effectiveness of the information pro-tection efforts.